2020
DOI: 10.1038/s41388-020-01478-7
|View full text |Cite
|
Sign up to set email alerts
|

The Scribble family in cancer: twentieth anniversary

Abstract: Among the more than 160 PDZ containing proteins described in humans, the cytoplasmic scaffold Scribble stands out because of its essential role in many steps of cancer development and dissemination. Its fame has somehow blurred the importance of homologous proteins, Erbin and Lano, all belonging to the LRR and PDZ (LAP) protein family first described twenty years ago. In this review, we will retrace the history of LAP family protein research and draw attention to their contribution in cancer by detailing the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 130 publications
(244 reference statements)
1
46
0
Order By: Relevance
“…The Scribble protein is a highly conserved cell polarity regulator comprising 16 Leucine-Rich Repeats and four PSD-95/Discs-large/ZO-1 (PDZ) domains and belongs to the LAP family of proteins [ 6 , 7 ]. Together with Discs Large (Dlg) and Lethal Giant Larvae (Lgl), Scribble acts to establish and maintain tissue homeostasis, as well as directed cell migration and tissue growth [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Scribble protein is a highly conserved cell polarity regulator comprising 16 Leucine-Rich Repeats and four PSD-95/Discs-large/ZO-1 (PDZ) domains and belongs to the LAP family of proteins [ 6 , 7 ]. Together with Discs Large (Dlg) and Lethal Giant Larvae (Lgl), Scribble acts to establish and maintain tissue homeostasis, as well as directed cell migration and tissue growth [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when considering certain determinants of the PDZ protein such as basolateral expression in epithelial cells, expression in the thyroid follicular cell, and class 1 PDZ‐binding motif recognition, one major candidate partner was identified, the PDZ protein SCRIB. SCRIB is a basolateral membrane‐associated PDZ multidomain scaffold protein containing 4 carboxy‐terminal PDZ domains involved in PDZ‐mediated protein–protein interactions 30 . SCRIB PDZ domains typically bind carboxy‐terminal class 1 PDZ‐binding motifs, and exhibit overlapping specificities for particular ligands, with each PDZ domain able to bind multiple interaction partners 31 .…”
Section: Resultsmentioning
confidence: 99%
“…SCRIB is a basolateral membrane-associated PDZ multidomain scaffold protein containing 4 carboxy-terminal PDZ domains involved in PDZ-mediated protein-protein interactions. 30 SCRIB PDZ domains typically bind carboxy-terminal class 1 PDZ-binding motifs, and exhibit overlapping specificities for particular ligands, with each PDZ domain able to bind multiple interaction partners. 31 Interestingly, PDZ Domain Arrays revealed that only SCRIB PDZ domains 1 and 4 strongly interact with NIS carboxy-terminus.…”
Section: The Pdz Protein Scrib Stabilizes Nis Expression At the Plasmmentioning
confidence: 99%
“…Together, these results suggest that subcellular localization of SCRIB, especially in nuclei and cytoplasm, might be important in the tumorigenic role of SCRIB, which warrants additional study. Loss of cell polarity protein might serve to induce tumors by promoting the uncontrolled proliferation of cells [28,29]. Therefore, as a component of polarity protein, SCRIB has been suggested as a tumor suppressor, and loss of SCRIB induced tumorigenesis in MYC-induced transformed epithelial cells [6].…”
Section: Discussionmentioning
confidence: 99%